Hubungan usia, lama kerja, dan postur kerja terhadap kejadian low back pain pada perawat rawat inap - Sudiono, Sudiono; Gowi, Abdul; Indrawati, Endah; Rosmaitaliza, Rosmaitaliza; Anisa , Nia (Holistik Jurnal Kesehatan, 2025)
Background: Low back pain (LBP) is one of the musculoskeletal disorders, one of the causes is due to non-ergonomic body posture. The prevalence of LBP according to Occupational Health ranges from 60-80% and this complaint is most often experienced by health workers, the incidence rate during a year in Western countries ranges from 36.2–57.9% and Asia ranges from 36.8–69.7%. Purpose: To determine the relationship between age, length of work and work posture with the incidence of low back pain in inpatient nurses. Method: Quantitative design with Cross Sectional approach. The number of samples used was 62 nurses in three inpatient rooms of Karawang Regional General Hospital (RSUD) who met the inclusion and exclusion criteria with total sampling technique. Data collection instruments used questionnaires and Rapid Entire Body Assessment (REBA) sheets with Chi-square statistical analysis. Results: The age of respondents was mostly ≥35 years as many as 41 respondents (66.1%). The length of service of respondents was mostly ≥10 years as many as 37 respondents (59.7%) and the work posture of respondents was mostly moderate risk as many as 32 respondents (51.6%). The results of bivariate analysis using the Chi-square test, on the age variable obtained a p-value of 0.049 <α (0.05), an Odds Ratio value of 3.142, and a Confidence Interval 95% CI of 1.142 - 12.021. The variable of length of work obtained a p-value of 0.022 <α (0.05), an Odds Ratio value of 4.156, and a CI 95% Confidence Interval of 1.349 - 14.801. The variable of work posture obtained a p-value of 0.000 <α (0.05), an Odds Ratio value of 0.091, and a CI 95% Confidence Interval of 0.027 - 0.307. Conclusion: There is a significant relationship between age, length of work, and work posture on the incidence of LBP with a p-value <0.05.   Keywords: Age; Low Back Pain; Nurses; Working Hours; Working Posture.   Pendahuluan: Low back pain (LBP) termasuk gangguan muskuloskeletal, salah satu penyebabnya karena postur tubuh yang tidak ergonomi. Prevalensi LBP menurut Occupational Health sekitar 60-80% dan keluhan ini paling sering dialami oleh tenaga kesehatan, angka insiden selama setahun di negara Barat berkisar 36.2–57.9% dan Asia berkisaran 36.8–69.7%. Tujuan: Untuk mengetahui hubungan usia, lama kerja dan postur kerja terhadap kejadian low back pain pada perawat rawat inap. Metode: Desain kuantitatif dengan pendekatan Cross Sectional. Jumlah sampel yang digunakan sebanyak 62 perawat di tiga ruang rawat inap Rumah Sakit Umum Daerah (RSUD) Karawang yang memenuhi kriteria inklusi dan eksklusi dengan teknik total sampling. Instrumen pengambilan data menggunakan kuesioner dan lembar Rapid Entire Body Assessment (REBA) dengan analisis statistik Chi-square. Hasil: Usia responden sebagian besar ≥35 tahun sebanyak 41 responden (66.1%). Lama bekerja responden sebagian besar ≥10 tahun sebanyak 37 responden (59.7%) dan postur kerja responden sebagian besar berisiko sedang sebanyak 32 responden (51.6%). Hasil analisis bivariat menggunakan uji Chi-square, pada variabel usia didapatkan p-value 0.049 < α (0.05), nilai Odds Ratio 3.142, dan CI 95% Confidence Interval 1.142 – 12.021. Variabel lama bekerja memperoleh p-value 0.022 < α (0.05), nilai Odds Ratio 4.156, dan CI 95% Confidence Interval 1.349 – 14.801. Variabel postur kerja memperoleh p-value 0.000 < α (0.05), nilai Odds Ratio 0.091, dan CI 95% Confidence Interval 0.027 – 0.307. Simpulan: Terdapat hubungan yang signifikan antara usia, lama kerja, dan postur kerja terhadap kejadian LBP dengan perolehan p-value <0.05.   Kata Kunci: Lama Kerja; Nyeri Punggung Bawah; Perawat; Postur Kerja; Usia.